Effectiveness and Economic Evaluation of Polyene Phosphatidyl Choline in Patients With Liver Diseases Based on Real-World Research - Fan, Jian-Gao; Li, Ying; Yu, Ze; Luo, Xing-Xian; Zheng, Ping; Hao, Xin; Wang, Ze-Yuan; Gao, Fei; Zhang, Guo-Qing; Feng, Wan-Yu (Frontiers in Pharmacology, 2022)
Aims: Liver disease has high prevalence, number and disease burden in China, and polyene phosphatidyl choline (PPC) is a widely used liver protective drug. We aim to explore the effectiveness and economy of PPC in patients with liver diseases based on real-world research, and compare with other hepatoprotective drugs. Methods: This is a "three-phase" study from three medical centers, including descriptive study of patients using PPC injection, self-control case study of patients using PPC injection, and specific-disease cohort study of patients using PPC injection or control drugs. The major measurements of liver function for effectiveness analysis was the alanine transaminase (ALT) level changes and recovery rate. The main statistical methods were Wilcoxon signed rank test, Chi-Square Test and Mann-Whitney U Test. Propensity score matching (PSM) was applied to reduce bias. Cost-effectiveness analysis, cost minimization analysis and sensitivity analysis were used for economic evaluation. Results: PPC alone or in combination with glutathione and magnesium isoglycyrrhizinate show less total hospitalization cost (p<0.05) and smaller cost effectiveness ratio and was effective in protecting liver function, especially in patients with liver transplantation or postoperation of non tumor liver disease (ALT decreased significantly after PPC treatment; p<0.05). Glutathione and magnesium isoglycyrrhizinate combined with PPC could enhance the protective function of liver. Conclusion: PPC was an effective and economic liver protective drug in patients with specific liver diseases, and PPC could enhance the liver protective function of glutathione and magnesium isoglycyrrhizinate.